Giant gastrointestinal stromal tumor of the mediastinum associated with an esophageal hiatal hernia and chest discomfort: a case report - Ryosuke Fujisawa; Yuji Akiyama; Takeshi Iwaya; Fumitaka Endo; Haruka Nikai; Shigeaki Baba; Takehiro Chiba; Toshimoto Kimura; Takeshi Takahara; Koki Otsuka; Hiroyuki Nitta; Masaru Mizuno; et al. (Surgical Case Reports)
Abstract Background Gastrointestinal stromal tumors (GISTs) grow relatively slowly and without specific symptoms; therefore, they are typically incidental findings. We report a rare gastric GIST in the mediastinum associated with chest discomfort and an esophageal hiatal hernia. Case presentation An 81-year-old woman with chest discomfort was admitted to the hospital, where barium esophagography showed a sliding esophageal hiatal hernia and a tumor of the lower esophagus and gastric wall. Esophagogastroscopy confirmed the presence of a huge submucosal tumor that extended from the lower esophagus to the gastric fundus. According to computed tomography, the mediastinal mass measured 12.7 cm and had heterogeneous low-density areas. A submucosal gastric tumor, which we suspected to be a GIST, was diagnosed in association with an esophageal hiatal hernia. Using thoracolaparotomy, we performed a total gastrectomy, a lower esophagectomy, and a Roux-en-Y reconstruction with the jejunum. The presumptive diagnosis was confirmed through immunohistochemical examination; immunostaining yielded results positive for CD34 and c-kit. The patient was discharged from the hospital 13 days after surgery with no complications and remained disease-free at follow-up 24 months after surgery. Conclusions GIST should be considered in the differential diagnosis of tumors growing in the mediastinum.